Selective effects of ligands on vitamin D3 receptor- and retinoid X receptor-mediated gene activation in vivo. - Lemon, B D (1996)
Steroid/nuclear hormone receptors are ligand-regulated transcription f factors that play key roles in cell regulation, differentiation, and oncogenesis. Many nuclear receptors, including the human 1,25-dihydroxyvitamin D3 receptor (VDR), bind cooperatively to DNA either as homodimers or as heterodimers with the 9-cis retinoic acid (RA) receptor (retinoid X-receptor [RXR]). We have previously reported that the ligands for VDR and RXR can differentially modulate the affinity of the receptors' interaction with DNA in vitro, primarily by modulating the dimerization status of these receptors. These experiments suggested a complex interaction between VDR and RXR and their respective ligands on inducible target genes in vivo. To examine these effects in cells, we used a transient-transfection strategy whereby we simultaneously introduced two different reporter plasmids that are selectively inducible by each ligand. Although VDR can bind as a homodimer to the osteopontin gene vitamin D response element, we find that a RXR-VDR heterodimer must be the transactivating species from the element in vivo, since RXR enhances and 9-cis RA and other RXR-specific ligands attenuate this induction. Conversely, when VDR is overexpressed, vitamin D3 attenuates 9-cis RA induction from an RXR-responsive element. These effects, however, appear to be very sensitive to both the relative ratios of the two receptors and their respective target elements. Functional RXR-VDR complexes are strictly dependent on the DNA-binding polarity. Chimeric versions of VDR and RXR were also constructed to examine the putative activities of homodimeric receptors; a VDR chimera can transactivate in the absence of RXR, demonstrating that VDR has intrinsic transactivation properties. Taken together, these results establish a complex, sensitive cross talk in vivo between two ligands and their receptors that signal through two distinct endocrine pathways.